The "Citizens for Activity" project - as an example of the management of sports projects influencing the marketing value of the region - Michalina Kuska; Mirosława Szark-Eckardt; Hanna Żukowska (Journal of Education, Health and Sport, 2017)
The aim of the work is to present the annual activities as well as their effects, as part of the "Citizens for Activity" project implemented by the Marshal's Office of the Kujawsko-Pomorskie Voivodeship, the Foundation for the Development of Physical Culture, the Center for Social Challenges of the University of Warsaw and the Run To Run Association. The aim of the project was to prepare a diagnosis of sport in the Kuyavian-Pomeranian region and then to create the Kujawsko-Pomorski Program for Sport Development. This undertaking is the first in Poland, so widely and long-term planned process of creating a voivodship program in this field. One of the main goals of the project was to develop elements of the marketing strategy and standards of funding and management of sports projects promoting the Kujawsko-Pomorskie voivodship. This article is a case study.